2023
DOI: 10.1186/s13765-022-00762-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity, flavor and physicochemical properties of FH06 functional beverage fermented by lactic acid bacteria: a promising method to improve antioxidant activity and flavor of plant functional beverage

Abstract: The ability of natural plants to treat chronic diseases is closely related to their antioxidant function. Lactic acid bacteria (LAB) fermentation is an effective way to improve the nutritional value, biological activity and flavor of food. This study investigated the pH, titratable acidity, total polysaccharide, total flavone, total saponin, total polyphenol, and antioxidant activity of the FH06 beverage before and after probiotic fermentation. Results: After fermentation, FH06 had lower contents of total poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, after fermentation by lactic acid bacteria, the content of cinnamaldehyde decreased from 3402.57 µg/L to 7.55 µg/L, and the OAV value dropped from 4.54 to 0.01, indicating that it was no longer a key compound in the flavor of the fermented beverage. Finally, the GCMS and sensory analysis of FH06 fermented by the GRX08 strain showed that fermentation removed the original grassy, tangerine peel, and bitter tastes, highlighting the fruity aroma and mild acidity, making the fermented FH06 more easily accepted by consumers [90].…”
Section: Improvements In Flavormentioning
confidence: 98%
“…However, after fermentation by lactic acid bacteria, the content of cinnamaldehyde decreased from 3402.57 µg/L to 7.55 µg/L, and the OAV value dropped from 4.54 to 0.01, indicating that it was no longer a key compound in the flavor of the fermented beverage. Finally, the GCMS and sensory analysis of FH06 fermented by the GRX08 strain showed that fermentation removed the original grassy, tangerine peel, and bitter tastes, highlighting the fruity aroma and mild acidity, making the fermented FH06 more easily accepted by consumers [90].…”
Section: Improvements In Flavormentioning
confidence: 98%
“…The fermentation broth of FH06 contains various types of compounds, including terpenes, alkaloids, organic acids and their derivatives, flavonoids, phenylpropanoids, phenols, aromatic compounds, and amino acid derivatives. Previous studies have shown that FH06 has a variety of effects, such as inhibiting lipase activity, α-glucosidase activity, and antioxidant activity in vitro, and has potential weight-loss and hypoglycemic effects [6]. However, the mechanism by which FH06 inhibits obesity has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests a complex interplay between reduced estrogen levels and obesity in menopausal women, indicating that estrogen deficiency is a contributing factor to weight gain [21]. Obesity is associated with an increased risk of type 2 diabetes, cardiovascular diseases, and osteoarthritis [22], leading the World Health Organization to designate it as a preventable cause of mortality [23]. Despite efforts to address obesity, its prevalence remains alarmingly high, with nearly one-third of the global population classified as overweight or obese in 2019 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Forest plant resources have been reported to exert antioxidant, anti-inflammatory, antibacterial, and antiviral effects through substances such as flavonoids, phenolic acids, and triterpenes such as maltol, chlorogenic acid, ellagic acid, and quercitrin [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%